2021
DOI: 10.1186/s12931-021-01679-y
|View full text |Cite
|
Sign up to set email alerts
|

Combined genomic and proteomic approaches reveal DNA binding sites and interaction partners of TBX2 in the developing lung

Abstract: Background Tbx2 encodes a transcriptional repressor implicated in the development of numerous organs in mouse. During lung development TBX2 maintains the proliferation of mesenchymal progenitors, and hence, epithelial proliferation and branching morphogenesis. The pro-proliferative function was traced to direct repression of the cell-cycle inhibitor genes Cdkn1a and Cdkn1b, as well as of genes encoding WNT antagonists, Frzb and Shisa3, to increase pro-proliferative WNT signaling. Despite these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 93 publications
(124 reference statements)
2
14
0
Order By: Relevance
“…Of note, few peaks overlapped between our data sets and that previously published for mouse lungs (Supplemental Fig. S3C; Lüdtke et al 2021), possibly because the genomic distribution of Tbx2 in lungs and melanoma are different, or because immunoprecipitation with anti-Tbx2 antibody may be less specific compared with use of anti-HA antibody. Moreover, because the previous study did not generate replicate ChIPs, we were uncertain of the reproducibility of the Tbx2 binding sites identified.…”
Section: Tbx2 Interacts With Non-t-element Targetssupporting
confidence: 48%
See 4 more Smart Citations
“…Of note, few peaks overlapped between our data sets and that previously published for mouse lungs (Supplemental Fig. S3C; Lüdtke et al 2021), possibly because the genomic distribution of Tbx2 in lungs and melanoma are different, or because immunoprecipitation with anti-Tbx2 antibody may be less specific compared with use of anti-HA antibody. Moreover, because the previous study did not generate replicate ChIPs, we were uncertain of the reproducibility of the Tbx2 binding sites identified.…”
Section: Tbx2 Interacts With Non-t-element Targetssupporting
confidence: 48%
“…Previous work to identify direct TBX2 target genes by ChIP-seq used an antibody against the endogenous protein. For example, using neuroblastoma cells, Decaesteker et al (2018) reported 557 TBX2 binding sites (q < 0.05) in total (41% intergenic; 30% lincRNAs; binding to consensus AGGTGTGA), while a more recent study of embryonic lungs (Lüdtke et al 2021) identified a total of 3062 Tbx2 peaks enriched >3.5-fold over the control, but only 177 were found within 5 kb of transcription start sites (TSSs), and in neither study were replicates used to robustly identify target sites. In contrast, by using high-affinity anti-HA antibody and HA-tagged endogenous Tbx2 in melanoma, we were able to identify up to 7500 binding sites (clone 9, R2) with a robust set of sites identified in common between multiple replicates, of which ∼38% were within 3 kb of the transcription start site.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations